Implementasi Metode Ekspresi Bebas dalam Menggambar sebagai Bentuk Ekspresi Diri Siswa pada Pembelajaran Seni Rupa Kelas IV SD - Zumrotul Isnaini, Ana; Setiawan, Deni (Universitas Muhammadiyah Magelang, 2026)
This study aims to describe the implementation of the free expression method in drawing as a form of self-expression among students in grade IV of Gubug 4 State Elementary School, Grobogan Regency. The study used a qualitative approach with a case study type. Data collection techniques included observation, interviews, and documentation. The study found that implementing the free expression method provided students with greater freedom to express ideas, feelings, and personal experiences through drawings. Students showed courage in choosing themes, colors, and drawing objects according to their respective imaginations. The form of student self-expression was seen through the diversity of works, symbols, and stories contained in the drawings. Supporting factors for the implementation of this method include the teacher's facilitative attitude and high student interest in drawing activities, while inhibiting factors include limited drawing tools and differences in student abilities.